2010
DOI: 10.1007/s11133-010-9152-2
|View full text |Cite
|
Sign up to set email alerts
|

Status Distinctions in Interaction: Social Selection and Exclusion at an Elite Nightclub

Abstract: Although social status plays a crucial role in the generation and maintenance of social inequalities, how status processes operate in naturalistic social contexts remains less clear. In the following article, I provide a case study of doormen-individuals who simultaneously represent status experts and status judges-at a highly exclusive nightclub to investigate how people draw status distinctions in micro-social settings. Using interview and ethnographic data, I analyze on what bases doormen evaluate the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 44 publications
3
78
0
Order By: Relevance
“…As indicated above, spatial exclusion, as a form of invisibilisation of particular ethnified bodies and troublesome masculinities, plays an important role in the attempt to enhance middle-class consumers and international elites' feeling of safety, comfort and freedom. These findings correlate with other studies of urban regeneration, which describe how governmental creation of attractive and safe consumer spaces in western cities is often coupled with the spatial exclusion of certain behaviors, bodies and signs of disorder (Hadfield, 2008;Boogaats, 2008;Measham & Hadfield, 2009;Samara, 2010;Rivera, 2010;Castro, 2013). At The Blue Palm, minority men were, however, not only rendered invisible through spatial exclusion; they were also rendered less socially visible to ethnic Danish consumers by being subjected to policies of compulsive integration designed to avoid ethnic enclavisation inside the venue.…”
Section: Making Troublesome Bodies Invisiblesupporting
confidence: 86%
See 2 more Smart Citations
“…As indicated above, spatial exclusion, as a form of invisibilisation of particular ethnified bodies and troublesome masculinities, plays an important role in the attempt to enhance middle-class consumers and international elites' feeling of safety, comfort and freedom. These findings correlate with other studies of urban regeneration, which describe how governmental creation of attractive and safe consumer spaces in western cities is often coupled with the spatial exclusion of certain behaviors, bodies and signs of disorder (Hadfield, 2008;Boogaats, 2008;Measham & Hadfield, 2009;Samara, 2010;Rivera, 2010;Castro, 2013). At The Blue Palm, minority men were, however, not only rendered invisible through spatial exclusion; they were also rendered less socially visible to ethnic Danish consumers by being subjected to policies of compulsive integration designed to avoid ethnic enclavisation inside the venue.…”
Section: Making Troublesome Bodies Invisiblesupporting
confidence: 86%
“…Research showed that bouncers regulate access on the basis of different criteria ranging from age, style of clothing, physical appearance (Hadfield, 2008), patrons' behavior, level of drunkenness and physical display of violent potential (Monaghan, 2003), formal and informal house rules, and patrons' history of violence (Hobbs et al, 2003). While Hobbs and his colleagues have focused on bouncers' policing of women, Hadfield (2008) and Rivera (2010) have described how class markers, race, accent and dress are central to bouncers' sorting practices at elite and prestigious venues. A central point put forward in this work is that bouncers regularly exclude ethnic or racial minorities, and that this is done either because ethnic or racial minorities are seen as less desirable consumers (Hadfield, 2008), or because they are seen as a threat to the ambience of more valued and affluent crowds (Measham & Hadfield, 2009).…”
Section: Inclusion and Exclusion In The Nightlife: An International Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Berger et al's (2002) status characteristic theory has seldom been used in the sociological study of bouncing and licensed establishments. A rare study that employs Berger et al's theory is Rivera's (2010) case study that explores the evaluation of patron status by bouncers who mediate access to an exclusive nightclub. Rivera examines the status characteristics used in the evaluative processes in a prestigious social setting and finds that the bouncers mainly evaluated patrons' visible status characteristics, such as race, accent, gender and dress (p. 248).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…It is crucial to study the use of evaluative processes in various social settings to determine whether or not the functioning of these processes depends on the type of establishment and the class of patrons being evaluated. Previous literature on the evaluation of status characteristics at licensed establishments has focused heavily on the evaluation of patron dress, age, physical appearance and gender (Rivera, 2010;Monaghan, 2002;May & Chaplin, 2008;Winlow et al, 2001). To date, there has been little to no scholarly focus on the status characteristic of patron attitude, the breaching of bouncer evaluations through bribery, or the lack of formal training and its impact on the development of bouncers' evaluation processes.…”
Section: Theoretical Frameworkmentioning
confidence: 99%